Islamic Education Teachers’ Perspectives on Religious Moderation Practices in Indonesian High Schools - Oktavia Fitriani; Hermawan, Wawan; Fakhruddin, Agus (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study aims to explain the perspectives of Islamic religious education teachers in understanding the concept of religious moderation, four indicators of religious moderation, the practice of implementing religious moderation, and the challenges faced during this implementation, as well as providing a broader understanding and perspective for Islamic religious education teachers regarding the practice of religious moderation. This study was conducted using a qualitative, phenomenological approach. Information was collected through in-depth interviews with Islamic religious education teachers. Data analysis was carried out in three stages: data reduction, data presentation or display, and drawing conclusions. The results show that teachers understand religious moderation as an attitude of balance, tolerance, respect for every difference, and rejection of all forms of extremism. The findings also indicate that Islamic religious education teachers have a positive perspective of religious moderation and have implemented it in the learning process. This study contributes to enriching the study of Islamic education by providing an empirical picture of Islamic religious education teachers’ perspective and practices of religious moderation in schools. Practically, the findings of this study have implications for strengthening the role of Islamic religious education teachers in integrating the values of religious moderation into the learning process to support tolerant and inclusive Islamic education.